Production of Probiotic Drink Using Pussy willow and Echium amoenum Extracts - Mahbobeh Eksiri; Leila Nateghi; Anosheh Rahmani (Applied Food Biotechnology, 2017)
Background and Objective: Nowadays, due to the lack of lactose and cholesterol, demand for consumption of non-dairy probiotic products is increasing. Probiotic drinks mixed with medicinal plant have great beneficial effect on human health. The main problems of non-dairy probiotic drinks are lack of nutrients for the growth of probiotics and bad taste of the product. The aim of this study was to produce a probiotic medicinal plant drink with favorable physicochemical, viability and sensory properties. Material and Methods: Probiotic drink prepared by Pussy willow and Echium amoenum extract (0.5 % w v-1, for each extract or together), Lactobacillus casei and Lactobacillus rhamnosus (108 CFU ml-1), individually and their combination. Glucose and whey powder (0.2%) were used as a source of nutrition for the probiotics, and apple juice (20 and 30%) was added to improve the taste of drink. The level of glucose was adjusted to reach the brix of 13 g100 g-1. Ascorbic acid (0.05%) was used to improve micro-aerophilic conditions. The pH, acidity, glucose and viability of probiotic bacteria as well as the sensory properties of the prepared drink were investigated during 28 days at 4°C. Results and Conclusion: Based on the results, the treatment containing L. casei, Pussy willow, Echium amoenum and 30% apple juice due to the highest probiotic viability and the treatment containing Lactobacillus rhamnosus, Pussy willow, Echium amoenum and 30% apple juice because of higher total acceptance score, proper pH and acidity values were selected as the best treatments. Conflict of interest: The authors declare no conflict of interest.